(NnOWYE RABOTY W OBLASTI REZANIQ METALLOW (B/s - (NlOMA^ENKOW(B, (Ns(B.(Nes ((NmOSKWAs (NlENINGRAD (B:s (NmA[GIZ(B,s, 1951)
(NzAKL(B.: (NS(B. 158s
(NlIT(B.: (NS(B. 158-159s
Keywords: (NrEZANIE METALLOWs